An evaluation of the variation and underuse of clozapine in the United Kingdom. (9th February 2021) - Whiskey, Eromona; Barnard, Alex; Oloyede, Ebenezer; Dzahini, Olubanke; Taylor, David M.; Shergill, Sukhwinder S.
Abstract: Background: Clozapine is the only licensed treatment for treatment refractory schizophrenia. Despite this, it remains grossly underused relative to the prevalence of refractory schizophrenia. The extent of underuse and the degree of regional variation in prescribing in the United Kingdom is unknown. It is also unclear, how the UK compares with other European countries in rates of clozapine prescribing. Methods: We obtained data relating to all clozapine prescribing in the UK from the relevant clozapine registries. We examined regional variation in clozapine use across England, corrected for the known prevalence of severe mental illness (SMI). We also compared the UK rate of clozapine use per 100, 000 population to that described in other European countries. Findings: There is substantial variation in clozapine prescribing across different regions of England and only about a third of potentially eligible patients were prescribed the drug in the UK. Clozapine prescribing rate in the UK was lower than in several European countries. Interpretation: There is clear regional inequity in access to the most effective treatment in refractory schizophrenia in England. Strategies to increase clozapine use, by overcoming both real and perceived barriers, are urgently necessary to reduce treatment inequity for patients with refractory schizophrenia.